2021
DOI: 10.3390/membranes11030207
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Monolithic MOF Thin Films in Acidic and Alkaline Aqueous Media

Abstract: In the context of thin film nanotechnologies, metal-organic frameworks (MOFs) are currently intensively explored in the context of both, novel applications and as alternatives to existing materials. When it comes to applications under relatively harsh conditions, in several cases it has been noticed that the stability of MOF thin films deviates from the corresponding standard, powdery form of MOFs. Here, we subjected SURMOFs, surface-anchored MOF thin films, fabricated using layer-by layer methods, to a thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…However, the amount of inhibitor release in the neutral solution is not significant. Also, the formation of Cu−OH in the alkaline solution leads to the destruction of the BMOF and the subsequent release of the 3‐AT inhibitor [45] . Therefore, it can be concluded that the carrier containing the inhibitor responses rapidly to the environmental stimuli (both acidic and alkaline pH) and releases a significant amount of 3‐AT.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the amount of inhibitor release in the neutral solution is not significant. Also, the formation of Cu−OH in the alkaline solution leads to the destruction of the BMOF and the subsequent release of the 3‐AT inhibitor [45] . Therefore, it can be concluded that the carrier containing the inhibitor responses rapidly to the environmental stimuli (both acidic and alkaline pH) and releases a significant amount of 3‐AT.…”
Section: Resultsmentioning
confidence: 98%
“…Also, the formation of CuÀ OH in the alkaline solution leads to the destruction of the BMOF and the subsequent release of the 3-AT inhibitor. [45] Therefore, it can be concluded that the carrier containing the inhibitor responses rapidly to the environmental stimuli (both acidic and alkaline pH) and releases a significant amount of 3-AT. Possible interactions between 3-AT and BMOF particles are shown in Figure 3C.…”
Section: Profile Of Loading and Ph-responsive Release Of The 3-at Cor...mentioning
confidence: 99%
“…The reports on the stability of UiO-66 and UiO-66-NH 2 in the acidic media, similar to the one, used in the present work for the polymerization (pH ≈ 2), are not conclusive. In the literature, ,, based on qualitative XRD data, it was reported that no considerable changes in the MOF diffraction patterns (and, thus, the crystallinity) were observed in low-pH conditions. However, at the same time, qualitatively indistinguishable changes in the XRD patterns can still be accompanied by a decrease in the MOF specific surface area (shown at pH 0 for both UiO-66 and UiO-66-NH 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…As recently investigated, the Zr-carboxylate UiO-66 MOF contains the water stable Zr 6 (µ 2 -O) 4 (µ 2 -OH) 4 clusters and robust Zr-carboxylate bonds, giving it high structural stability against hydrolysis in a wide pH range. 17,25,26 On the other hand, it appears that the high cytotoxicity of ZIF-8 can be linked to its poor structural stability in neutral to slightly acidic environment. 26 To further assess this hypothesis, a control experiment was designed and conducted, where the cytotoxicity of the two components of ZIF-8, namely Zn(II) ions and 2-methylimidazole (MI), were separately assessed on HeLa, THP1, and U937 cell lines.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…17,25,26 On the other hand, it appears that the high cytotoxicity of ZIF-8 can be linked to its poor structural stability in neutral to slightly acidic environment. 26 To further assess this hypothesis, a control experiment was designed and conducted, where the cytotoxicity of the two components of ZIF-8, namely Zn(II) ions and 2-methylimidazole (MI), were separately assessed on HeLa, THP1, and U937 cell lines. As shown in Fig.…”
Section: Biomaterials Science Papermentioning
confidence: 99%